Urgensi Sertifikat Keandalan Privasi Dalam Menghadapi Kebocoran Data Pribadi - Zandra Azelia Savitri; Muhamad Amirulloh; Mei Susanto (Jurnal USM Law Review)
This study examines the urgency of privacy reliability certificates in addressing the increasing prevalence of personal data breaches due to the rapid advancement of information and communication technology. In Indonesia, data breaches have significantly increased, with nearly 160 million personal data records exposed since 2004. These breaches have severe consequences, including identity theft and declining public trust in electronic systems. Although Law No. 27 of 2022 on Personal Data Protection has been enacted, its implementation and data security mechanisms remain suboptimal. This research adopts a normative juridical approach to analyze the legal standing of privacy reliability certificates under Law No. 20 of 2014 on Standardization and Conformity Assessment, as well as the legal obligations of electronic system operators in ensuring data security. The findings reveal that privacy reliability certificates are not yet mandatory for non-strategic electronic system operators in Indonesia, unlike in developed countries where similar certifications are required to enhance cybersecurity. The government should accelerate the adoption of privacy reliability certificates as a national standard (SNI) to strengthen personal data protection, increase transparency, and provide legal certainty for electronic system operators and users.